Pengaruh Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Puninar Yusen Logistik Di Jakarta - Siti Roudotul Wahda; Bayu Seno Pitoyo; Dewi Sri Woelandari Giningroem (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to determine the effect of job stress and work discipline on employee performance at PT Puninar Yusen Logistics in Jakarta. This research uses a quantitative approach. The sampling technique used is non probability sample, namely saturated sample with 32 respondents. The results showed that partially work stress did not have a significant effect on employee performance at PT Puninar Yusen Logistics in Jakarta, and work discipline had a partially significant effect on employee performance at PT Puninar Yusen Logistics in Jakarta, and simultaneously work stress and work discipline had a significant effect on employee performance at PT Puninar Yusen Logistics in Jakarta.